2022
DOI: 10.5483/bmbrep.2022.55.12.141
|View full text |Cite
|
Sign up to set email alerts
|

Stress granules dynamics: benefits in cancer

Abstract: Stress granules (SGs) are stress-induced subcellular compartments, which carry out a particular function to cope with stress. These granules protect cells from stress-related damage and cell death through dynamic sequestration of numerous ribonucleoproteins (RNPs) and signaling proteins, thereby promoting cell survival under both physiological and pathological condition. During tumorigenesis, cancer cells are repeatedly exposed to diverse stress stimuli from the tumor microenvironment, and the dynamics of SGs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 105 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…[ 37,38 ] Previous studies have reported that SGs influence the malignant behavior of tumors, particularly their invasion, migration, and drug resistance. [ 12,16 ] Our research showed that ICC stimulated with E. coli exhibited enhanced migratory ability and chemoresistance. A significant increase in the number of SGs was observed.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…[ 37,38 ] Previous studies have reported that SGs influence the malignant behavior of tumors, particularly their invasion, migration, and drug resistance. [ 12,16 ] Our research showed that ICC stimulated with E. coli exhibited enhanced migratory ability and chemoresistance. A significant increase in the number of SGs was observed.…”
Section: Discussionmentioning
confidence: 84%
“…[10] Stress granules (SGs) play a crucial role in cell survival during bacterial infection by responding to microenvironmental stimuli. [11][12][13] These granules protect cells from stress-induced damage and death by sequestering numerous ribonucleoprotein particles (RNPs) and signaling proteins. [14,15] This mechanism is essential for promoting cell survival under physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SGs are dynamically regulated (Protter & Parker, 2016). It occurs under stress conditions or cancer drug treatment and usually disappears after recovery from stress (Lee & Namkoong, 2022). Tumors are often faced with stressful environments.…”
Section: Discussionmentioning
confidence: 99%